Analisis Gelar Perkara dalam Proses Penyidikan Tindak Pidana Di Kepolisian - Fajar Sudariyanto; Helvis Helvis; Wasis Susetio (Jurnal Syntax Transformation, 2021)
This study describes the important role of the case title process in the settlement of criminal cases, especially in the police, to find out the case title process carried out by investigators in uncovering criminal cases to the process of stopping investigations and to find out the obstacles experienced by investigators in carrying out case titles. Then also to find out what are the legal consequences in the case of a legally flawed case, whether in the end it can be pre-trial. The research method used is a type of normative legal research conducted by reviewing library materials or secondary materials. Normative research aims at systematizing, correcting and clarifying the applicable legal rules in certain legal fields by conducting an analysis of authoritative texts that include primary and secondary legal materials as well as ensuring consistent and consistent law. The data source consists of primary data, namely the results of interviews and then analyzed. The primary legal material used is related to the investigation of criminal acts by the police, namely Law no. 8 of 1981 the Criminal Procedure Code, the Chief of Police Regulation, and the Criminal Procedure Code. The results of the study indicate that the case title is carried out to provide legal status for handling cases, so that the settlement process does not experience errors in decision making, which will affect the process of handling criminal cases. The inhibiting factors for the implementation of case titles are the time that is not possible if all criminal cases are carried out with a Case Title, the costs are quite high while the budget is inadequate, the number of investigators in the police is not sufficient, the author's suggestion is that the rules regarding the title of cases in the police are made in detail in the Criminal Procedure Code